Strategies to promote intermittent self-catheterisation in adults with neurogenic bladders: A comprehensive systematic review - Adams, J.; Watts, Robin; Yearwood, M.; Watts, A.; Hartshorn, C.; Simpson, S.; Allingham, K.; Denison, S.; Hardcastle, B. (University of Adelaide, 2011)
Executive Summary: Background: Clean intermittent self‐catheterisation is the gold standard in the management of neurogenic/neuropathic bladder disorders, providing independence, alleviating symptoms and complications of the urinary tract. Objectives: The objective of this systematic review was to establish the best available evidence on strategies to promote intermittent urethral self‐catheterisation in adults with neurogenic/neuropathic bladders. Methods: The search strategy identified published and unpublished studies reported from 1970 to 2009. Individual search strategies were developed for the 12 databases accessed and search alerts established. The review considered qualitative and quantitative studies, mixed methods and case studies. Interventions, programs and strategies preparing adults to self‐catheterise included education, suitability for self-catheterisation and interventions promoting compliance and continuity. Outcomes of interest were the quality of life and depression, long‐term compliance, advantages/disadvantages of urethral self‐catheterisation and limitations to self-catheterisation. Standardised critical appraisal instruments developed by the Joanna Briggs Institute were used by two independent reviewers to assess the quality of eligible studies for inclusion in the review. Standardised Joanna Briggs Institute tools were also used to extract data. Criteria developed by Yin were employed to assess case studies. Qualitative findings were synthesised. As statistical pooling of the quantitative results was not possible, these results were presented in narrative form.Results: From the 18 studies reviewed, three interventions (education and preparation, suitability to self‐catheterise, and interventions promoting compliance/continuity), and three outcomes (effect of self‐catheterisation on quality of life and depression, and long-term compliance) were addressed with multiple studies in each intervention and outcome. The results are discussed under four headings: (i) education essentials for self-catheterisation (ii) factors promoting compliance and continuity with self‐catheterisation, (iii) factors influencing quality of life and (IV) diagnostic sub‐groups of people with a neurogenic bladder. Conclusion: The narrative and synthesised data from the 18 included studies identified findings to provide a basis for strategies to promote clean intermittent self‐catheterisation in adults. These include an extended education program with a pre‐education component, ongoing support and skills training. All aspects of education should reflect sound research findings related to quality of life issues. Implications for Practice: The implications for clinical practice are the development of a comprehensive standardised education program that includes background information, skills training and follow‐up support. Implications for Research: The review highlights the need for further experimental research to confirm factors that will promote self‐catheterisation in adults with neurogenic/neuropathic bladders, with particular reference specific sub‐groups.